Pengaruh Struktur Modal, Profitabilitas, dan Ukuran Perusahaan Pada Nilai Perusahaan Farmasi yang Terdaftar di BEI Tahun 2018 - 2021 - Ida Bagus Kediri Wibawa Putra; M. Wahyullah; Putri Reno Kemala sari (Akuntabel: Jurnal Ilmiah Akuntansi, 2024)
This study aims to analyze the Effect of Capital Structure, Profitability, and Company Size on the Value of Companies Listed on the Indonesia Stock Exchange in 2018-2021. The type of research used in this study is associative research. The variables of this study consist of 3 (Three) independent variables, namely Capital Structure (X1), Profitability (X2), and Company Size (X4), and the dependent variable is Company Value (Y). The population in this study is all pharmaceutical companies listed on the Indosesia Stock Exchange from 2018 to 2021. Samples were taken using purposive sampling of 8 companies. The data analysis method used is multiple linear regression analysis using SPSS application version 23. The results of this study show that, Capital Structure, Profitability, and Company Size have no effect on the value of the Company. This result also shows that the independent variables, namely Capital Structure (X1), Profitability (X2), and Company Size (X3) are able to explain the dependent variable, namely company value (Y) by 5.0%. While the remaining 95.0% is influenced by other variables.